Lumbar plexus block: Safe anesthesia for hip surgery - Sarkar (Mitra), T. (Medknow Publications & Media Pvt Ltd, 2012)
General anesthesia and neuraxial blockade have their own advantages and disadvantages over each other when used for hip surgery. Single shot lumbar plexus block can be the choice of the anesthetic technique for postrenal transplant, immunocompromised, postspinal surgery patient to undergo dynamic hip screw surgery.